ANALISIS PERBAIKAN JARINGAN JALAN KEC. LEMBANG-NGAMPRAH KABUPATEN BANDUNG BARAT (RUAS JALAN KOLONEL MASTURI) TERHADAP TINGKAT KENYAMANAN, KESELAMATAN, DAN KEAMANAN JALAN. - Eky Aprian Cakra Lesmana, - (2021)
Colonel Masturi road section is a road that connects Ngamprah sub-district with Lembang sub-district, West Bandung regency. The function of the Jalan Kolonel Mastrui section is as a collector road with mountainous terrain. Jalan Kolonel Masturi is used to relieve congestion in the city of Bandung. Drivers from the Jabodetabek direction who want to go to the Lembang area do not need to enter the city of Bandung first, therefore the role of the Colonel Masturi road is very important in breaking down congestion in the city of Bandung. However, in fact, as reported by the National Transportation Safety Committee in 2016, there was a bus accident that resulted in 9 deaths and 7 serious injuries and 23 minor injuries. To improve the quality of traffic services, it is necessary to analyze the repair of the road network to reduce the level of accidents that occur on the Colonel Masturi road. To find out how much traffic volume is on the Kolonel Mastrui road section, an analysis of the generation and attraction of the movement is carried out using the multiple linear regression analysis method with SPSS. It is known that the total traffic volume in 2051 is 1900.57 pcu/hour. To respond to the capacity problem, it is necessary to widen the road and geometric redesign on the Kolonel Masturi road so that it can be passed safely and comfortably.